POLICIES & PROCEDURES IN FEDERAL CIVILIAN PROCUREMENT. - Linnenberg, Clem C. (The Accounting Review, 1943)
Abstract The U.S. Federal Government uses both definite and indefinite-quantity contracts, the latter being known also as "term contracts" and "open-end contracts." An indefinite-quantity contract ordinarily is one by which the government promises that, during a stated period, a specified agency or group of agencies will buy certain specified commodities only from a particular supplier. The supplier promises that he will sell to the agency or agencies as little or as much as they wish to buy of those commodities during the period named. A minimum-quantity contract differs from an indefinite-quantity contract only in involving a commitment by the government as to the minimum amount that it will buy. The Procurement Division of the U.S. Treasury Department is the nearest approach which Federal procurement has to centralized buying. It effects or aids in a far smaller percentage of the War and Navy Departments' total purchases than of civilian agencies' total purchases, and at present is of course overshadowed, in importance as a buying agency, by each of the former two agencies' vastly increased procurement.